Implementasi Manajemen Risiko Bencana bagi Anak Berkebutuhan Khusus di Sekolah Luar Biasa (SLB) Negeri 1 Yogyakarta - Tanggela, Stephani Jecquelin Daindo; Bawole, Paulus; Nainggolan, Freddy Marihot Rotua (ATRIUM: Jurnal Arsitektur, 2025)
Title: The Implementation of Disaster Risk Management for Children with Special Needs at Sekolah Luar Biasa Negeri 1 Yogyakarta Disaster risk reduction for children with special needs in special schools is an important thing that needs to be implemented because children with special needs are a vulnerable group when a disaster occurs. This research employs a qualitative descriptive method, collecting data through observation, interviews, documentation, literature reviews, and behavior mapping. This research uses the III Pillars of Comprehensive School Safety and Behaviour Mapping as the basis of analysis. The study was conducted to know the implementation of disaster risk management by SLB Negeri 1 Yogyakarta and the response of children with special needs.  SLB Negeri 1 Yogyakarta has conducted disaster risk reduction through several aspects, namely facilities, disaster management, and disaster education. However, in the implementation, there are still shortcomings generally caused by land limitations.  The behavior mapping process reveals that the adaptable responses demonstrated by students with special needs make any aspect that does not meet the standard tolerable.